2017
DOI: 10.1261/rna.061119.117
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-responsive miRNAs in Drosophila orchestrate adaptation to different ambient temperatures

Abstract: The majority of genes are expressed in a temperature-dependent manner, but the way in which small RNAs may contribute to this effect is completely unknown as we currently lack an idea of how small RNA transcriptomes change as a function of temperature. Applying high-throughput sequencing techniques complemented by quantitative real-time PCR experiments, we demonstrate that altered ambient temperature induces drastic but reversible changes in sequence composition and total abundance of both miRNA and piRNA popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 65 publications
2
32
2
Order By: Relevance
“…We have tested if such stresses were able to convert BX2 OFF into BX2 ON in one generation but neither heat-shock nor osmotic stress induces BX2 conversion (TABLE S9), suggesting that BX2 activation does not depend on dATF-2. In a more recent paper, Fast et al (34) found less piRNAs at 29°C than at 18°C. However, RNAseq analyses of differentially expressed genes involved in the piRNA pathway were not conclusive, as some piRNA genes were more expressed at 29°C (ago3, aub, zuc, armi) while others were less expressed (shu, hsp83, Yb) (34).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…We have tested if such stresses were able to convert BX2 OFF into BX2 ON in one generation but neither heat-shock nor osmotic stress induces BX2 conversion (TABLE S9), suggesting that BX2 activation does not depend on dATF-2. In a more recent paper, Fast et al (34) found less piRNAs at 29°C than at 18°C. However, RNAseq analyses of differentially expressed genes involved in the piRNA pathway were not conclusive, as some piRNA genes were more expressed at 29°C (ago3, aub, zuc, armi) while others were less expressed (shu, hsp83, Yb) (34).…”
Section: Discussionmentioning
confidence: 92%
“…In a more recent paper, Fast et al (34) found less piRNAs at 29°C than at 18°C. However, RNAseq analyses of differentially expressed genes involved in the piRNA pathway were not conclusive, as some piRNA genes were more expressed at 29°C (ago3, aub, zuc, armi) while others were less expressed (shu, hsp83, Yb) (34). Overall, the enhancement of the piRNA pingpong amplification loop observed at 29°C was attributed to RNA secondary structures, because of a lack of specificity for any particular class of TE (34).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Based on the observation that temperature-responsive genes were enriched for miRNA target sites it was further assumed that miRNAs could play a critical role in temperature-dependent gene regulation. To test this hypothesis, we have recently sequenced and analyzed ovary expressed small RNAs and mRNA from Drosophila cohorts kept at 18 C and 29 C. We further subjected each cohort to a temperature shift from 18-to-29 C or 29 C-to-18 C, respectively, to investigate the dynamics of putative expression changes [4]. We were able to verify profound and reversible changes in miRNA expression patterns and additionally showed that the expression levels of temperature-responsive miRNAs and their predicted target genes correlate inversely ( Fig.…”
Section: Temperature Shapes Drosophila Phenotypesnew Thoughts To An Omentioning
confidence: 99%